The LINC00961 transcript and its encoded micropeptide, small regulatory polypeptide of amino acid response, regulate endothelial cell function. Issue 12 (28th January 2020) - Spencer, Helen L; Sanders, Rachel; Boulberdaa, Mounia; Meloni, Marco; Cochrane, Amy; Spiroski, Ana-Mishel; Mountford, Joanne; Emanueli, Costanza; Caporali, Andrea; Brittan, Mairi; Rodor, Julie; Baker, Andrew H
Abstract: Aims: Long non-coding RNAs (lncRNAs) play functional roles in physiology and disease, yet understanding of their contribution to endothelial cell (EC) function is incomplete. We identified lncRNAs regulated during EC differentiation and investigated the role of LINC00961 and its encoded micropeptide, small regulatory polypeptide of amino acid response (SPAAR), in EC function. Methods and results: Deep sequencing of human embryonic stem cell differentiation to ECs was combined with Encyclopedia of DNA Elements (ENCODE) RNA-seq data from vascular cells, identifying 278 endothelial enriched genes, including 6 lncRNAs. Expression of LINC00961, first annotated as an lncRNA but reassigned as a protein-coding gene for the SPAAR micropeptide, was increased during the differentiation and was EC enriched. LINC00961 transcript depletion significantly reduced EC adhesion, tube formation, migration, proliferation, and barrier integrity in primary ECs. Overexpression of the SPAAR open reading frame increased tubule formation; however, overexpression of the full-length transcript did not, despite production of SPAAR. Furthermore, overexpression of an ATG mutant of the full-length transcript reduced network formation, suggesting a bona fide non-coding RNA function of the transcript with opposing effects to SPAAR. As the LINC00961 locus is conserved in mouse, we generated an LINC00961 locus knockout (KO) mouse that underwent hind limb ischaemia (HLI) to investigate the angiogenic role of this locus in vivo . In agreement with in vitro data, KO animals had a reduced capillary density in the ischaemic adductor muscle after 7 days. Finally, to characterize LINC00961 and SPAAR independent functions in ECs, we performed pull-downs of both molecules and identified protein-binding partners. LINC00961 RNA binds the G-actin sequestering protein thymosin beta-4x (Tβ4) and Tβ4 depletion phenocopied the overexpression of the ATG mutant. SPAAR binding partners included the actin-binding protein, SYNE1. Conclusion: The LINC00961 locus regulates EC function in vitro and in vivo . The gene produces two molecules with opposing effects on angiogenesis: SPAAR and LINC00961 . Graphical Abstract: